Factors influencing the selection of delivery with no one present in Northern Nigeria: implications for policy and programs - Fapohunda, Bolaji (Dove Medical Press, 2014)
This paper examines the effects of demographic, socioeconomic, and women’s autonomy factors on the utilization of delivery assistance in Sokoto State, Nigeria. Data were obtained from the Nigeria 2008 Demographic and Health Survey (DHS). Bivariate analysis and logistic regression procedures were conducted. The study revealed that delivery with no one present and with unskilled attendance accounted for roughly 95% of all births in Sokoto State. Mothers with existing high risk factors, including higher parity, were more likely to select unsafe/unskilled delivery practices than younger, lower-parity mothers. Evidenced by the high prevalence of delivery with traditional birth attendants, this study demonstrates that expectant mothers are willing to obtain care from a provider, and their odds of using accessible, affordable, skilled delivery is high, should such an option be presented. This conclusion is supported by the high correlation between a mother’s socioeconomic status and the likelihood of using skilled attendance. To improve the access to, and increase the affordability of, skilled health attendants, we recommended two solutions: 1) the use of cash subsidies to augment women’s incomes in order to reduce finance-related barriers in the use of formal health services, thus increasing demand; and 2) a structural improvement that will increase women’s economic security by improving their access to higher education, income, and urban ideation.